Keratinocytes and neutrophils are important sources of proinflammatory molecules in hidradenitis suppurativa. (1st March 2016) - Lima, A.L.; Karl, I.; Giner, T.; Poppe, H.; Schmidt, M.; Presser, D.; Goebeler, M.; Bauer, B.
Summary: Background: The pathogenesis of the chronic inflammatory skin disease hidradenitis suppurativa (HS, also known as acne inversa) involves epidermal alterations such as psoriasiform epidermal hyperplasia and keratin plugging. Keratinocytes are an important source of proinflammatory molecules in inflammatory skin diseases and can be stimulated by interleukin (IL)‐17 + cells. Objectives: To explore the possible role of the epithelium in the pathogenesis of HS. Methods: We performed immunohistochemical stainings and Western blot experiments to investigate the localization and expression of inflammation‐associated molecules, including the cytokine IL‐17, components of the inflammasome including caspase‐1, and the endogenous danger‐associated molecular pattern molecules S100A8 and S100A9 (calprotectin). To examine a possible effect of upregulated proinflammatory cytokines on the inflammatory infiltrate, differences in the cellular composition of perifollicular and deep dermal infiltrates were analysed. Results: The number of IL‐17 + cells is increased in lesional and perilesional HS skin. The epidermis produces proinflammatory molecules and shows an upregulated expression of components of the NLRP3 inflammasome, activated caspase‐1 and expression of S100A8/S100A9. Additionally, the course of the inflammatory process in HS involves influx of innate immune cells, particularly IL‐17‐expressing neutrophils. Conclusions: IL‐17‐producing cells are present in lesional and perilesional HS skin and may contribute to the initiation of inflammatory processes. Furthermore, the epidermis is a source of proinflammatory cytokines, shows inflammasome activation and expresses S100A8/S100A9, thereby possibly contributing to the propagation of inflammation. A massive influx of IL‐17‐expressing neutrophils is observed in the deep infiltrate.